Sociology of Anti-Violence Education at Ma Ma'arif Nu 1 Kemranjen: A Study of Religious Language, Masculinity, and Disciplined Culture - Muruatul luthfiyah; Muh. Hanif (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2026)
This critical qualitative study examines the practice of anti-violence education at MA Ma’arif NU 1 Kemranjen, which still grapples with institutional disciplinary culture, religious rhetoric, and constructions of masculinity. The findings reveal a distinct ambivalence: on one hand, verbal and physical violence are frequently normalized under the guise of discipline and moral language; on the other hand, religious values are utilized by teachers to instill compassion and reject violence. Furthermore, the construction of student masculinity concurrently triggers group dominance and fosters peer solidarity. This study concludes that anti-violence education in madrasas requires a critical deconstruction of disciplinary culture and masculinity, which are often legitimized by religious narratives.